2002
DOI: 10.1046/j.1365-2036.2003.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant lactoferrin is ineffective in the treatment of human Helicobacter pylori infection

Abstract: SUMMARYBackground: Lactoferrin, a multifunctional glycoprotein, is known to have anti-microbial actions. Bovine lactoferrin and recombinant human lactoferrin have been shown to inhibit Helicobacter pylori, and more recently recombinant human lactoferrin was found to significantly increase the eradication rate of H. pylori when added to standard triple therapy. Aim: To determine the efficacy, safety and tolerability of recombinant human lactoferrin as a therapy in suppressing or eliminating H. pylori infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In addition, human recombinant LF (250 or 1000 mg doses, 5 times over a 24 h period) when ingested on its own did not allow eradication of H. pylori in 12 healthy subjects infected with the bacteria [101]. Similar results were reported, also showing no effect of human recombinant LF administration (1000 mg, 5 times for 5 or 14 days) on H. pylori in humans [48]. Consumption of fermented milk has been linked with a reduction in H. pylori infection in humans.…”
Section: Antimicrobialrole Of Milk Proteins In Humanssupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, human recombinant LF (250 or 1000 mg doses, 5 times over a 24 h period) when ingested on its own did not allow eradication of H. pylori in 12 healthy subjects infected with the bacteria [101]. Similar results were reported, also showing no effect of human recombinant LF administration (1000 mg, 5 times for 5 or 14 days) on H. pylori in humans [48]. Consumption of fermented milk has been linked with a reduction in H. pylori infection in humans.…”
Section: Antimicrobialrole Of Milk Proteins In Humanssupporting
confidence: 68%
“…Milk protein consumption has also been shown to have potential in increasing muscle protein synthesis in humans [32,135]. However, certain human intervention studies have failed to demonstrate health promoting effects following milk protein consumption [48,103].…”
Section: Introductionmentioning
confidence: 99%
“…21 Guttner et al administrated 5 g recombinant human LF per day for 5 or 14 days, and found neither conversion of the UBT from positive to negative nor consistent decrease of UBT values with a possible suppression of H. pylori. 22 In contrast to the inefficacy of recombinant human LF, oral administration of bLF (200 mg b.i.d) in combination with a 7-day triple eradication regime (rabeprazole, clarithromycin, and tinidazole) was successful to eradicate H. pylori in 100% of patients, whereas the triple therapy eradication regimen without bLF was only effective in 76.9%. 14 Although there was no conversion of the UBT value from positive to negative (as in the two recombinant human LF studies), administration of the same dosage of bLF alone was effective for reducing the density of H. pylori colonizing the stomach in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…tears, bile and saliva) [116] that showed bacteriostatic and bactericidal effects [117,118] . Human lactoferrin, as a single agent, does not eradicate H. pylori infection as was demonstrated by a recent study performed in vivo in 9 patients [119] . Conversely, bovine lactoferrin could have synergistic actions if employed with PPI and antibiotics as showed in two clinical trials [120,121] .…”
Section: Rescue Therapies After Two or More Failuresmentioning
confidence: 74%